PENGARUH KEJELASAN SASARAN ANGGARAN, KETIDAKPASTIAN LINGKUNGAN DAN PENGENDALIAN AKUNTANSI TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH DENGAN KINERJA MANAJERIAL SEBAGAI VARIABEL MODERASI (Studi Empirit Pada SKPD Kota pekanbaru) - Hirdri Azelya Lestari Sembiring; Vince Ratnawati; Rusli Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this study was to examine the effect of budget objective clarity, environmental uncertainly, and accounting controls on goverment performance accountability. We also examine the effect of managerial performance as moderating variable. All of the population as the sample and we found amounted 92 respondens. Data analysis technique used is multiple regression analysis were processed with SPSS. The result of this study show that budget objective clarity and accounting controls has positive significant effect on performance accountability, while environmental uncertainly has negative significant effect on performance accountability. Personal managerial performance moderates the relationship between budget objective clarity and accounting controls on performance accountability. Otherwise, personal managerial performance does not moderate the relationship between environmental uncertainly on performance accountability.Keywords : budget, environmental, controls, managerial, and accountability